(untitled) (Nepalese Linguistics, 2022)
This presidential address raises issues in language policy of Nepal regarding multiple official languages in the government business. Implementation of this policy requires language of record and a group of government staff to work on different languages. By creating jobs for hundreds of linguists, this solution addresses the university officials’ concern about decreasing number of students in linguistics.